2022
DOI: 10.1007/s40272-022-00500-7
|View full text |Cite
|
Sign up to set email alerts
|

Slower Recovery with Early Lopinavir/Ritonavir use in Pediatric COVID-19 Patients: A Retrospective Observational Study

Abstract: Objectives There was initially insufficient understanding regarding suitable pharmacological treatment for pediatric Coronavirus Disease 2019 (COVID-19) patients. Lopinavir-ritonavir (LPV/r) was originally used for the treatment of Human Immunodeficiency Virus-1 (HIV-1) infection. It was also used in patients with severe acute respiratory syndrome (SARS) and Middle East Respiratory Syndrome (MERS) with positive results. Nonetheless, results from recent randomized controlled trials and observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Electronic medical records of all admitted patients with COVID-19 confirmed by positive reverse transcription polymerase chain reaction (RT-PCR) test were collected from the Hospital Authority database for the study period from January 21st, 2020 to January 31st, 2021, including patient demographics, deaths, diagnoses, procedures, drug prescription and dispensing history, and laboratory test results. The Hospital Authority database has been used extensively for the evaluation of drug therapies for COVID-19 ( Wong et al, 2021a ; Wong et al, 2021b ; Wong et al, 2022a ; Wong et al, 2022b ). The follow-up period lasted until April 30th, 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Electronic medical records of all admitted patients with COVID-19 confirmed by positive reverse transcription polymerase chain reaction (RT-PCR) test were collected from the Hospital Authority database for the study period from January 21st, 2020 to January 31st, 2021, including patient demographics, deaths, diagnoses, procedures, drug prescription and dispensing history, and laboratory test results. The Hospital Authority database has been used extensively for the evaluation of drug therapies for COVID-19 ( Wong et al, 2021a ; Wong et al, 2021b ; Wong et al, 2022a ; Wong et al, 2022b ). The follow-up period lasted until April 30th, 2021.…”
Section: Methodsmentioning
confidence: 99%
“…However, Elmekaty et al [ 41 ] showed that early treatment with LPV/r is associated with a faster clinical improvement and/or virological clearance than the darunavir/cobicistat therapy in patients with COVID-19 pneumonia, and that the safety profile was quite comparable. Finally, Wong et al [ 42 ] discourage the use of LPV/r for pediatric COVID-19 cases because of their negative clinical outcomes, reporting a longer time for clinical improvement, seroconversion, hospital discharge, together with a higher risk of a hyperinflammation.…”
Section: Antiviral Drugsmentioning
confidence: 99%